2018
DOI: 10.1016/j.ergon.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of injuries to front-end loader operators during ingress and egress

Abstract: Slips, trips, and falls from mobile mining equipment have been documented for decades. However, little research has been conducted to determine the events precipitating these incidents during ingress or egress. This study examined slips, trips, and falls sustained during ingress or egress from front-end loaders to determine the frequencies of factors that may contribute to injuries. Non-fatal injuries, when getting on or off of front-end wheel loaders specifically, were identified, coded, and analyzed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…This is consistent with injury data from mobile mining equipment and general ladder use. Nasarwanji et al (2018) determined that over 60% of the STF injuries to mining front-end loader operators occur during egress, 25% occur during ingress, and another 11% occur during maintenance or other activities. Santos et al (2010) found a similar proportion in mining haul truck operators, with 46% of all non-fatal injuries to haul truck operators occurring during egress and 23% occurring during ingress.…”
Section: Egressmentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with injury data from mobile mining equipment and general ladder use. Nasarwanji et al (2018) determined that over 60% of the STF injuries to mining front-end loader operators occur during egress, 25% occur during ingress, and another 11% occur during maintenance or other activities. Santos et al (2010) found a similar proportion in mining haul truck operators, with 46% of all non-fatal injuries to haul truck operators occurring during egress and 23% occurring during ingress.…”
Section: Egressmentioning
confidence: 99%
“…One study found that most falls from mobile mining equipment occur during ingress (climbing into the cab from the floor/ground) or egress (exiting from the cab to the floor/ground) (Moore et al, 2009). A recent analysis of STFs from front-end loaders during ingress and egress revealed that over 60% of the injuries occur during egress and 25% occur during ingress (Nasarwanji et al, 2018). This is slightly higher than statistics previously reported for haul truck operators, where most nonfatal injuries (46%) occurred during egress, with a smaller but still large portion (23%) having occurred during ingress (Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations